Firms in international trade - Federico J. Díez; Jesse Mora; Alan C. Spearot (Federal Reserve Bank of Boston, 2016)
Firms play a critical role in the global economy. In this paper, we survey the behavior of firms in the international economy, both in theory and in the data. We first summarize the key empirical facts that motivate the study of firms in trade. Then, we detail recent theoretical developments on the micro-foundations of firm behavior in an international context, focusing on how firms select into exporting, and how firms respond to international shocks. Finally, we turn to a "real world", empirically focused view of exporting, beginning with the growth dynamics of firms expanding to global markets, and then addressing the critical financing decisions firms make when engaging in international commerce. We conclude with directions for future research.
Keywords: F10; F12; F14; 330; firm heterogeneity; international trade; exporters